Prosthetic Joint Infection Due to “Helcococcus pyogenica” - Panackal, Anil A. (American Society for Microbiology, 2004)
Helcococci have previously been associated with the colonization of ulcers and infections of the skin and soft tissues. We describe a case of prosthetic joint infection due to a previously undescribed organism that is genetically most closely related to Helcococcus.